Functionalisation of flaxseed proteins assisted by ultrasonication to produce coatings enriched with raspberries phytochemicals. (April 2020) - Juodeikiene, Grazina; Zadeike, Daiva; Trakselyte-Rupsiene, Karolina; Gasauskaite, Kotryna; Bartkiene, Elena; Lele, Vita; Viskelis, Pranas; Bernatoniene, Jurga; Ivanauskas, Liudas; Jakstas, Valdas
Abstract: This study was dedicated to the functionalisation of flaxseed proteins by ultrasonication to produce coatings enriched with flaxseed proteins and raspberry phytochemicals. High frequency (850 kHz) ultrasound (US) was used for the texturization of flaxseed proteins at 50 °C temperature. The functional properties of proteins (emulsifying, foaming, and gelling) significantly ( p < 0.05) depended on the medium pH and US intensity. High intensity (2 W/cm 2 ) US resulted in a significant changes of the electrophoretic pattern of albumins and globulins by formation of small (<12 kDa) components. In the case of albumins, the emulsion formation capacity (EFC) was the highest with the lowest US intensity ( 1 W/cm 2 ) and at pH 3. A significant increase in foam formation capacity (FFC) within globulin fractions was found with the lowest US intensity (0.9 W/cm 2 ) and at pH 7. By using a 15% suspension rich in protein flaxseed fraction, a more homogeneous structure of the gel and more effective gelling was achieved when using US treatment at 1.3 W/cm 2 intensity compared to 0.9 W/cm 2 . Additional results showed potential improvements in the colour and functionality of flaxseed protein coatings by adding up to 9% of the formulation of the RPC fraction enriched with ellagic acid. Highlights: Low power ultrasound was applied for flaxseed protein gel structuring. The functional properties of proteins significantly depend on pH and ultrasound power. Low power ultrasound enhanced functional properties of flaxseed proteins. The emulsifying properties of albumins was the best at pH 3. The highest foaming capacity of globulins was at pH 7.